Internationale Studienergebnisse (Praxis Handreha, 2024)
Griffiths GS, Thompson BL, Snell DL et al. Person-centred management of upper limb complex regional pain syndrome: an integrative review of non-pharmacological treatment. Hand Therapy 2023; 28: 16–32